Pengembangan LKPD IPAS Berbasis Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Romadhon Hafild, M. Nazali; Putri, Tiya Permana; Pramudiyanti, Pramudiyanti; Dewi, Pramita Sylvia (STKIP PGRI Bandar Lampung, 2024)
Creative thinking ability is one of the High Order Thinking Skill (HOTS). This ability is an important part of developing learning in the 21st century based on technological advances, especially communication and information technology. IPAS is one of the new subjects contained in the Merdeka curriculum, providing teachers with the opportunity to develop teaching materials to answer the challenges of changing the 21st century learning mindset. One of the teaching materials developed is Discovery Learning-based LKPD which aims to improve students' creative thinking skills. The purpose of this study was to determine the process of developing Discovery Learning-based LKPD IPAS. The development model used is a modified 4D model, while the research subjects are fourth grade students of SDN 02 Tambahrejo Pringsewu. From the results of the validity and effectiveness tests conducted, it was found that the Discovery Learning-based IPAS LKPD was valid and effective for use in improving students' creative thinking skills.